Experimental investigation of liquid chromatography columns by means of computed tomography - Astrath, Dirk-Uwe; Lottes, Florian; Arlt, Wolfgang; et al. (Adsorption-Journal of the International Adsorption Society, 2007)
The efficiency of packed chromatographic columns was investigated experimentally by means of computed tomography (CT) techniques. The measurements were carried out by monitoring tracer fronts in situ inside the chromatographic columns. The experimental results were fitted using the equilibrium dispersive model (EDM) and varying the so called apparent axial dispersion coefficient. The additivity of the first and second central moments was exploited to estimate column efficiency in different regions of the column. The results showed that the columns under investigation offered a higher column efficiency in the centre compared to the wall region. Furthermore the void fraction in the vicinity of the walls was lower than that in the column core. For this reason the bands were conveyed faster in the central region of the column where the permeability was higher. This result is in good agreement with earlier findings. © Springer Science+Business Media, LLC 2007.
Keywords: Chromatography; Computed tomography (CT)